Sex-Specific Effects of Nanoparticle-Encapsulated MitoQ (nMitoQ) Delivery to the Placenta in a Rat Model of Fetal Hypoxia - Ganguly, Esha; Aljunaidy, Mais M.; Kirschenman, Raven; Spaans, Floor; Morton, Jude S.; Phillips, Thomas E. J.; Case, C. Patrick; Cooke, Christy-Lynn M.; Davidge, Sandra T. (Frontiers in Physiology, 2019)
Pregnancy complications associated with chronic fetal hypoxia have been linked to the development of adult cardiovascular disease in the offspring. Prenatal hypoxia has been shown to increase placental oxidative stress and impair placental function in a sex-specific manner, thereby affecting fetal development. As oxidative stress is central to placental dysfunction, we developed a placenta-targeted treatment strategy using the antioxidant MitoQ encapsulated into nanoparticles (nMitoQ) to reduce placental oxidative/nitrosative stress and improve placental function without direct drug exposure to the fetus in order to avoid off-target effects during development. We hypothesized that, in a rat model of prenatal hypoxia, nMitoQ prevents hypoxia-induced placental oxidative/nitrosative stress, promotes angiogenesis, improves placental morphology, and ultimately improves fetal oxygenation. Additionally, we assessed whether there were sex differences in the effectiveness of nMitoQ treatment. Pregnant rats were intravenously injected with saline or nMitoQ (100µl of 125 μM) on gestational day (GD) 15 and exposed to either normoxia (21% O2) or hypoxia (11% O2) from GD15-21. On GD21, placentae from both sexes were collected for detection of superoxide, nitrotyrosine, nitric oxide, CD31 (endothelial cell marker) and fetal blood spaces, Vegfa and Igf2 mRNA expression in the placental labyrinth zone. Prenatal hypoxia decreased male fetal weight which was not changed by nMitoQ treatment; however, placental efficiency (fetal/placental weight ratio) decreased by hypoxia, and was increased by nMitoQ in both males and females. nMitoQ treatment reduced the prenatal hypoxia-induced increase in placental superoxide levels in both male and female placentae but improved oxygenation in only female placentae. Nitrotyrosine levels were increased in hypoxic female placentae and were reduced by nMitoQ. Prenatal hypoxia reduced placental Vegfa and Igf2 expression in both sexes while nMitoQ increased Vegfa and Igf2 expression only in hypoxic female placentae. In summary, our study suggests that nMitoQ treatment could be pursued as a potential preventative strategy against placental oxidative stress and programming of adult cardiovascular disease in offspring exposed to hypoxia in utero. However, sex differences need to be taken into account when developing therapeutic strategies to improve fetal development in complicated pregnancies, as nMitoQ treatment was more effective in placentae from females compared with males.